Tingkat Kondisi Fisik Dominan terhadap Kemampuan Bermain Bola Voli pada Siswa Binaan Ekstrakurikuler MAS Tgk. Chiek Oemar Diyan Kab. Aceh Besar - Agung Gunedi Rs; Zikrur Rahmat; Tawakal Tawakal (Jurnal Pustaka Cendekia Pendidikan, 2026)
Volleyball performance is strongly influenced by physical condition components that support the effective execution of fundamental techniques. School extracurricular coaching requires objective information regarding students' physical condition to design appropriate training programs and improve athletic achievement. This study aimed to analyze the dominant physical condition affecting volleyball playing ability among students participating in the volleyball extracurricular program at MAS Tgk. Chiek Oemar Diyan, Aceh Besar Regency. This study employed a quantitative approach using a survey design. The population consisted of 14 students, all of whom were selected as the research sample through the total sampling technique. Data were collected using the medicine ball throw, vertical jump, side step test, wall toss test, and a volleyball skills test. Data were analyzed using descriptive statistics and the coefficient of determination with IBM SPSS Statistics. The results revealed that the students' dominant physical condition was generally categorized as good (42.86%), while their volleyball playing ability was also classified as good (35.71%). The adjusted R square value of 0.491 indicated that physical condition contributed 49.1% to volleyball playing ability, whereas the remaining 50.9% was influenced by other factors beyond the scope of this study. It can be concluded that systematic physical conditioning should be integrated with technical, tactical, and mental training to optimize volleyball performance and enhance students' athletic achievement.